LIBMAN-SACKS ENDOCARDITIS IN A SYSTEMIC LUPUS ERYTHEMATOSUS MALE PATIENT - Fauqa Arinil Aulia; Sidarti Soehita (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Libman-Sacks endocarditis (verrucous vegetations, marantic, or nonbacterial thrombotic endocarditis) is a rare cardiac manifestation in SLE. The objective was to describe Libman-Sacks endocarditis in a SLE male patient. A 21-year-old male was admitted to the hospital with shortness of breath, epigastric pain, oral ulcer, discoid lesions, and knee joints pain since 3 months before. He worked as a paper mill employee and was exposed to instruments radiating UV rays for 2 years. Antibiotics initiation was given due to an infective endocarditis suspicion. Vital signs were as follows: temperature 37oC, heart rate 110beats/minute, respiratory rate 30breaths/minute, blood pressure 100/80mmHg, and SaO2 99% with nasal oxygenation. Cardiac examination showed regular rate and rhythm with diastolic murmur at left ICS III and upper left sternal border. Lower extremities showed pitting edema. Laboratory results: hemoglobin 9.6g/dl, RBC 3.6x106/Î¼l, hematocrit 30.8%, WBC 0.88x103/Î¼l, platelet count 22x103/Î¼l, BUN 74.0mg/dl, serum creatinine 1.6mg/dl, ESR 24mm/h, CRP 1.2mg/dl, C3 <16.4mg/dl, C4 8mg/dL, ANA test indeterminate (23.84), and anti dsDNA negative (7.4WHOunits/mL). Chest X-Ray showed mitral heart configuration with right ventricle and left atrium enlargement, pneumonia, and right pleural effusion. ECG showed normal sinus rhythm, left ventricular hypertrophy with repolarization abnormality, and prolonged QT wave. A 2-D echocardiogram showed an evidence of vegetation on aortic and pulmonary valve. Based on the American College of Rheumatology SLE Criteria, low complement level, and evidence of vegetation on aortic and pulmonary valve, the patient was diagnosed as Libman-Sacks Endocarditis. The diagnosis should be confirmed by antiphospholipid antibodies examination.